Pendekatan Konseptual Terhadap Faktor-Faktor Dalam Kinerja Organisasi - Stenly Ronaldo Titioka; Baretha M Titioka; Astrid J.D. Siahainenia (P3M Politeknik Negeri Ambon, 2024)
Organization which is a collection of people who have the same goal. What happens to the organization and employees when the world around them is changing so fast? The organizational structure, remuneration system, resource management practices, leadership styles used in the 1900s or 1960s do not necessarily correspond anymore to the current environment or the symptoms that arise in the 21st century. The purpose of this study is to find out whether the Variable Leadership, Organizational Culture and Strategy effect on productivity. Based on the study of theoretical and empirical studies the conclusions of this research can be stated in more detail (more detailed) that: (1) Leadership and Organizational Culture bias each influences; (2) The effect on Strategy Leadership Organization; (3) Cultural Organization affect the strategy of the Organization; (4) Leadership and organizational culture affect the strategy of the Organization; (5) Leadership, Organizational Culture and Organizational Strategies effect on employee productivity. Key Words: Leadership, Organizational Culture, Organizational Strategy, and Employee Productivity.